Morphology of the cardiovascular system in greater rhea (Rhea americana americana Linnaeus, 1758) - Araújo Júnior, Hélio Noberto; Bezerra, Ferdinando Vinícius Fernandes; Oliveira, Radan Elvis Matias; Costa, Herson Silva; Oliveira, Gleidson Benevides; Moura, Carlos Eduardo Bezerra; Pereira, Alexsandra Fernandes; Assis Neto, Antônio Chaves; Oliveira, Moacir Franco (Medicina Veterinária, 2021)
Greater rheas (Rhea americana americana) have been the subject of scientific studies in the various areas of veterinary and biology in order to obtain essential information for their captivity management. The aim of this study was to describe the morphology of the greater rhea heart. The 20 animals were incised in sagittal plane, then fixed in 10% formaldehyde and dissected after 72 h. In addition, samples from the cardiovascular system were collected, processed for hematoxylin-eosin and Gomori Trichrome Staining. The heart is conical in shape, dark red when fresh and is located between the hepatic lobes. It has two atria and two ventricles, and four valves (left and right atrioventricular, aortic and pulmonary semilunar). The aorta and pulmonary trunk emerge at the heart base, while the ostia of the cranial and caudal vena cava emerged from the right atrium and the right and left pulmonary veins and the left coronary vein from the left atrium. From the aorta artery, the right and left coronary arteries arose, which originated, respectively, the superficial and conal branches and the profuse, left ventricular and superficial branches, being responsible for the irrigation of the heart. Microscopically the heart was constituted by simple pavement epithelium, rich in loose connective tissue. The aorta and pulmonary arteries were composed of the intima, middle and adventitial tunics. Thus, it is concluded that the morphological findings of greater rhea resemble those described for other birds such as ostrich and chicken.